Analysis of Translation Errors in CNN Indonesia News Texts Into Arabic Through Perplexity.Ai Application - Umam, Ahmad Zaimul; Ridlo, Akhmad; Farisi, Mohamad Zaka Al; Ali, Mad (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2024)
Perplexity.ai is very helpful in the world of translation. This study aims to analyze the translation errors produced by Perplexity.ai from morphological, syntactic, and semantic aspects. This research is a descriptive qualitative method. The data analysis technique of this research uses a content analysis technique. This study examines the translation errors of CNN Indonesia's news entitled